Single service points in libraries: A review. Issue 2 (2nd April 2016) - Frederiksen, Linda; Wilkinson, Brandon
ABSTRACT: As libraries of all types and sizes continue to re-envision themselves to remain relevant in a rapidly changing information landscape, the single service point is visible evidence of this effort. In a complex environment, combining formerly disparate functional or service units is for many libraries both an innovative and effective way to manage resources and services. It is the intent of this overview to look beyond these issues to find similarities in theme and application that may be useful for those considering implementation of a one-stop model.